2013
DOI: 10.1111/j.1552-6569.2012.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

FLAIR Distal Hyperintense Vessels as a Marker of Perfusion‐Diffusion Mismatch in Acute Stroke

Abstract: DHV may be a surrogate marker for PDM in patients with hyperacute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 13 publications
(42 reference statements)
0
45
0
Order By: Relevance
“…In univariate analysis, patients with PWI-DWI mismatch had lower initial NIHSS scores (15 [range, [11][12][13][14][15][16][17][18][19][20] , P ϭ .01), and lower serum glucose levels at admission (6.7 Ϯ 1.2 versus 7.3 Ϯ 1.8 mmol/L, P ϭ .04). In multivariate analysis based on easily derivable admission variables, PWI-DWI mismatch was independently associated with FVH-DWI mismatch (OR, 7.63; 95% CI, 1.74 -33.43; P ϭ .007) after adjustment for onset-to-admission MR imaging time (OR, 0.98; 95% CI, 0.97-1.00; P ϭ .02) and DWI-ASPECTS (OR, 1.76; 95% CI, 1.22-2.53; P ϭ .003).…”
Section: Identification Of Pwi-dwi Mismatchmentioning
confidence: 99%
See 2 more Smart Citations
“…In univariate analysis, patients with PWI-DWI mismatch had lower initial NIHSS scores (15 [range, [11][12][13][14][15][16][17][18][19][20] , P ϭ .01), and lower serum glucose levels at admission (6.7 Ϯ 1.2 versus 7.3 Ϯ 1.8 mmol/L, P ϭ .04). In multivariate analysis based on easily derivable admission variables, PWI-DWI mismatch was independently associated with FVH-DWI mismatch (OR, 7.63; 95% CI, 1.74 -33.43; P ϭ .007) after adjustment for onset-to-admission MR imaging time (OR, 0.98; 95% CI, 0.97-1.00; P ϭ .02) and DWI-ASPECTS (OR, 1.76; 95% CI, 1.22-2.53; P ϭ .003).…”
Section: Identification Of Pwi-dwi Mismatchmentioning
confidence: 99%
“…After an intracranial arterial occlusion, FLAIR vascular hyperintensities (FVHs) are seen in 45%-100% of patients with stroke. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Although their pathophysiologic and clinical significance is not fully understood, FVHs might help in the management of patients with acute stroke. Beyond their diagnostic value regarding the detection of arterial occlusion, 11,14,15 FVHs may provide prognostic information, despite discrepancies among studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that FHVs are prominent within the Sylvian fissure. [6][7][8][9][10][11][12][13][14][15] This might be because the larger arteries have a slower flow speed than the smaller distal arteries under the same perfusion pressure. Hohenhaus et al 6 reported that…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Recently, distal FHVs have been studied more due to their clinical importance. 6,7 Technically, in the setting of normal hemodynamics, the blood vessels show dark signal intensity on spin-echo sequences such as FLAIR because of the dephasing effect from mixed spinechoes and stimulated echoes, as well as the disrupted spin-echo mechanism due to through-plane blood motion. The retrograde slow flow results in the loss of this flow void phenomenon, and vessels appear hyperintense against the dark CSF background.…”
mentioning
confidence: 99%